Meningkatkan Keaktifan dan Motivasi Peserta Didik Melalui Pembuatan Mading pada Materi Keanekaragaman Hayati di Kelas lV SD: Improving the Activity and Motivation of Students Through the Creation of Bulletin Boards on Biodiversity Materials in Grade IV Elementary School - Rahmalia Putri Aras; Azizah; Ni Made Erviniati (STKIP Subang, 2025)
Through the creation of wall magazine (madding) about biodiversity materials, this classroom action research aims to improve the activity and desire of fourth-grade elementary school students to learn. A total of 25 students participated in the study. Planning, action, observation, and reflection are the three research cycles used. The tools employed are observation sheets for student activity and a questionnaire about their motivation. The questionnaire was administered in the first and third cycle to assess how much students’ desire to learn has change. The findings showed that students’ activeness improved in every cycle, increasing from 28% in the pre-cycle to 40% in the first cycle, 68% in the second cycle, and reaching 88% in the third cycle. Students learning motivation also significantly increased, with the average score rising from 2.6 in the first cycle to 3.55 in the third cycle. Thus, the use of wall magazine ad a project-based learning medium is effective in improving students’ activeness and learning motivation in science lessons for elementary school students.